The Role of Trade in Ending Poverty - World Bank Group; World Trade Organization (Geneva: World Trade Organization, 2015)
The expansion of international trade has been essential to development and poverty reduction. Todays economy is unquestionable global. Trade as a proportion of global GDP has approximately doubled since 1975. Markets for goods and services have become increasingly integrated through a fall in trade barriers, with technology helping drive trade costs lower. But trade is not an end in itself. People measure the value of trade by the extent to which it delivers better livelihoods, through higher incomes, greater choice, and a more sustainable future, among other benefits. For the extreme poor living on less than $1.25 a day, the central value of trade is its potential to help transform their lives and those of their families. In this way, there is no doubt that the integration of global markets through trade openness has made a critical contribution to poverty reduction. The number of people living in extreme poverty around the world has fallen by around one billion since 1990. Without the growing participation of developing countries in international trade, and sustained efforts to lower barriers to the integration of markets, it is hard to see how this reduction could have been achieved.